Analysis of correlations between contents of protein fractions in wheat endosperm models and their mechanical resistance. (September 2016) - Budny, J.A.; Fornal, J.; Obuchowski, W.
Abstract: The mechanical strength of wheat endosperm and its laboratory models is determined by the types and contents of endosperm components. Studies on endosperm models enable controlling contents of endosperm components and then determining correlations between the model's components and their mechanical resistance. In this article we present a research on correlations between contents of protein fractions and mechanical resistance of wheat endosperm models. In contrast to previous reports, we showed that the starch fraction was the main factor influencing the mechanical resistance of the analyzed models. Simultaneously, we demonstrated no correlations between the contents of protein fractions in starch and a wheat hardness index. In addition, we showed some correlations between contents of protein fractions in the models and their mechanical resistance. However, these correlations were so weak that they should be treated as secondary. Highlights: Inter-varietal differences were analyzed for protein contents in an endosperm fraction. Endosperm models were made with an inter-varietal exchange of flour fractions. Mechanical resistance of the endosperm models was measured. No correlations were found between protein content and mechanical resistance. Structural components of starch strongly affect the mechanical strength of the analyzed models.